Optimization of Growth and Yield of Melon Plants (Cucumis melo L.) in Drip Irrigation Hydroponic System by Providing Various Planting Media and Doses of Magnesium Sulfate Fertilizer - Firdi Ihza Rochman; Didik Utomo Pribadi; Felicitas Deru Dewanti (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Melon is a horticultural commodity with high sales value in both local and export markets. Consumer demand for sweet, fresh, and high-quality melons continues to rise. This rising demand for melons requires higher productivity. To achieve higher melon productivity, advanced agricultural cultivation technologies are required, including hydroponic melon cultivation. This study aims to determine the effects of planting media and magnesium sulfate fertilizer doses on the growth and yield of hydroponic melons using a drip irrigation system. The study was conducted at the Puspa Lebo greenhouse, Lebo Village, Sidoarjo District, Sidoarjo Regency, East Java, from September to November 2024. The research employed a Completely Randomized Design (CRD) with two treatment factors. The first factor was the type of planting media, consisting of three treatments: rice husk charcoal, cocopeat, and a 1:1 mixture of rice husk charcoal and cocopeat. The second factor was the magnesium sulfate fertilizer dose, with four treatments: 0 g/plant, 15 g/plant, 30 g/plant, and 45 g/plant. The results indicated that the rice husk charcoal planting medium treatment affected the fruit weight parameter. Meanwhile, the Magnesium fertilizer dose treatment of 15 g/plant affected plant length and leaf number. The use of rice husk charcoal as a planting medium increased melon fruit weight, and it is recommended that further research explore its advantages for use with other commodities.